RESILIENCE, HAPPINESS AND LIFE SATISFACTION AMONG LECTURERS AT RIVERS STATE UNIVERSITY - Wadi, Elizabeth Oghenetega; Marire-Nwankwo, Chinenye (African Journal of Social and Behavioural Sciences, 2025)
The study examined the extent to which resilience predicts life satisfaction, ascertained the extent to which happiness predicts life satisfaction, and determined the extent to which resilience and happiness jointly predict the life satisfaction of lecturers in Rivers State University. The study adopted a correlational survey design. Primary data were used for the study. Data were collected from lecturers at Rivers State University. The sample for this study consisted of 147 lecturers, who were selected through the stratified random sampling technique. Three standardised psychological scales were used in the study: The Satisfaction with Life Scale (SWLS), the Resilience Scale (RS), and the stratified random sampling technique. The results show that there was a positive significant relationship between resilience and life satisfaction (r = .17, p<.05). The result shows that there was a positive significant relationship between happiness and life satisfaction (r = .19, p<.05). Also the result revealed that there was significant joint prediction of resilience and happiness on life satisfaction F(2, 147) = 4.92, R2 = .06; p<.05). The R2 =.06 which indicates that the independent variables resilience and happiness explained 6% variation in dependent variable (Life satisfaction). Further results showed that resilience (β= .17; t= 2.09; p<.05) and happiness (β= .19; t= 2.35; p<.05) independently predict life satisfaction among lecturers at Rivers State University. The study concluded that resilience and happiness were factors that predicted life satisfaction among Lecturers in Rivers State.